2021
DOI: 10.1155/2021/9921012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Macrophage Polarization-Related Genes as Biomarkers of Chronic Obstructive Pulmonary Disease Based on Bioinformatics Analyses

Abstract: Objectives. Chronic obstructive pulmonary disease (COPD) is characterized by lung inflammation and remodeling. Macrophage polarization is associated with inflammation and tissue remodeling, as well as immunity. Therefore, this study attempts to investigate the diagnostic value and regulatory mechanism of macrophage polarization-related genes for COPD by bioinformatics analysis and to provide a new theoretical basis for experimental research. Methods. The raw gene expression profile dataset (GSE124180) was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…A recent transcriptional analysis compared peripheral blood samples from patients with chronic obstructive pulmonary disease (COPD) with normal controls. The results suggested that GEM is related to COPD and macrophage polarization [ 26 ]. This adds to the suggestion that MPO-ANCA may have a specific role in the pathogenesis of lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent transcriptional analysis compared peripheral blood samples from patients with chronic obstructive pulmonary disease (COPD) with normal controls. The results suggested that GEM is related to COPD and macrophage polarization [ 26 ]. This adds to the suggestion that MPO-ANCA may have a specific role in the pathogenesis of lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…These datasets and gene sets formed the basis of our study to investigate the relationship between MPRGs and HCC prognosis. 21 …”
Section: Methodsmentioning
confidence: 99%
“…The relationships between each module and trait data were investigated using Pearson's correlation analysis to obtain the key module. The gene signi cance (GS, |GS|>0.2) and module membership (MM, |MM|>0.8) values of the modules were calculated, and the signi cantly-related module genes were screened [21].…”
Section: Screening Of Differential Immune Cellsmentioning
confidence: 99%